How Hate Crime Legislation Shapes Gay and Lesbian Target Groups: An Analysis of Social Construction, Law, and Policy: - Valcore, Jace L. (Criminal justice policy review, 2019)
Supporters of hate crime legislation argue the laws are a positive development designed to promote social equality and encourage political participation. Critics claim the laws are patronizing and disempowering. Existing research addresses neither the impact of hate crime laws on designated social groups nor attempts to verify assumptions about legislation and the social and political status of protected minorities. Sexual orientation, one of the most controversial categories, resulted in considerable social and political debate. This research explores the addition of sexual orientation to state hate crime law and how inclusion of this target group affects the social construction of gays and lesbians. Data are drawn from a sample of 12 daily newspapers in six states. Content and time-series analyses were used to explore social construction. The results indicate that inclusion in hate crime protections fails to have a positive impact on the construction of the group, and the discussion offers important policy implications.